2000
DOI: 10.1111/j.1349-7006.2000.tb01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Granulocyte Colony‐stimulating Factor and Parathyroid Hormonerelated Protein Production in Lung Carcinoma Cell Line OKa‐C‐1

Abstract: Previously we have established a clonal squamous cell carcinoma cell line OKa‐C‐1 derived from lung cancer of a patient with marked leukocytosis and hypercalcemia. OKa‐C‐1 cells simultaneously produce granulocyte colony‐stimulating factor (G‐CSF) and parathyroid hormone‐related protein (PTHrP) at the single cell level and cause paraneoplastic syndromes in nude mice bearing the tumor. It is known that the production of G‐CSF and PTHrP is individually regulated by inflammatory cytokines in various malignant cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The following eight cytokines were evaluated: Parathyroid hormone-related protein (PTHrP) 23 , tumor necrosis factor (TNF)-a 13 , interleukin (IL)-1a 3 , IL-1b 3 , IL-6 3 , IL-11 8 , IL-18 11 and transforming growth factor (TGF)-b 10 ( Table 1).…”
Section: Immunohistochemical Staining Of Cytokines Related To Bone Rementioning
confidence: 99%
“…The following eight cytokines were evaluated: Parathyroid hormone-related protein (PTHrP) 23 , tumor necrosis factor (TNF)-a 13 , interleukin (IL)-1a 3 , IL-1b 3 , IL-6 3 , IL-11 8 , IL-18 11 and transforming growth factor (TGF)-b 10 ( Table 1).…”
Section: Immunohistochemical Staining Of Cytokines Related To Bone Rementioning
confidence: 99%
“…[36][37][38] We have previously demonstrated that IL-1β and TNF-α significantly stimulate G-CSF production by the tumor cell line OKa-C-1. 39) In this study, we showed that both cytokines also significantly enhanced G-CSF production by MI-4 cells. MI-4 cells produced neither TNF-α nor IL-1β themselves.…”
Section: Discussionmentioning
confidence: 56%
“…[38][39][40] We showed that the inflammatory cytokines, TNF-α and IL-1β induced COX-2 expression in addition to G-CSF or GM-CSF in OKa-C-1 and MI-4 cells. 27,41) Some studies have reported that NF-κB activa- tion is required to upregulate G-CSF, GM-CSF, or COX-2 expression, [42][43][44][45][46][47][48][49] and that inactivation of the NF-κB also induces rapid pro-apoptotic action. 45) COX-2 activation was also shown to follow the activation of MAPK in another cell type.…”
Section: Discussionmentioning
confidence: 99%